Study of the effect of basic parameters on the efficiency of wireless transmission electricity (Latakia University Journal -Basic Sciences Series, 2019)
In this search the affecting factors on wireless electricity transfer and efficiency studied using flat spiral coil and impedance matching in order to improve the efficiency of electricity transfer by changing transfer distance. The Parameter of electricity transfer that effect in transfer technology analyzed and studied. Implementation and Realization are accomplished the using circuit. Addition to, the experimental measurement was achieved and compared with the theoretical model. At the result the experimental measurements were well matched to the theoretical calculations. We found that the efficiency increases by increasing the quality factor of the coils and decreases by increasing the transfer distance. We measured the maximum efficiency for variable transmission distances between internal coils starting from 30cm up to 130 cm. The results also showed that increasing the response frequency of coils does not necessarily increase the quality factor of the coils.